Synthesis and characterization of gadolinium-doped ZnSe quantum dots for fluorescence imaging of cancer cells. Issue 19 (8th February 2016) - Sureshkumar, S.; Jothimani, B.; Sridhar, T. M.; Venkatachalapathy, B.
Abstract : Gadolinium-doped ZnSe (Gd:ZnSe) quantum dots (Qds) were synthesized using ethylene glycol as a stabilizing agent. Abstract : Gadolinium-doped ZnSe (Gd:ZnSe) quantum dots (Qds) were synthesized using ethylene glycol as a stabilizing agent. The fluorescence spectrum exhibited an emission peak at 435 nm for ZnSe, whereas the Gd-doped ZnSe exhibited a green emission at 547 nm. In vitro imaging studies of MCF-7 cancer cells were carried out using fluorescent probes constructed using Gd-ZnSe folate.